2016
DOI: 10.1111/all.12871
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β1-induced transcription factor networks in Langerhans cell development and maintenance

Abstract: Langerhans cells (LC) represent a specialized subset of evolutionarily conserved dendritic cells (DC) that populate stratified epithelial tissues, which are essential for the induction of skin and mucosal immunity and tolerance, including allergy. TGF-β1 has been confirmed to be a predominant factor involved in LC development. Despite great advances in the understanding of LC ontogeny and diverse replenishment patterns, the underlying molecular mechanisms remain elusive. This review focuses on the recent disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
0
14
0
Order By: Relevance
“…Given that Runx proteins interact with Smad proteins ( Ito and Miyazono, 2003 ), Smad family proteins potentially interact with Runx3/Cbfβ2 complexes to regulate LC differentiation during BMP7-BMPR1A signaling. Although Smad2, Smad3, and Smad4 are not required for LC differentiation in vivo ( Xu et al, 2012 ; Li et al, 2016 ; Zhang et al, 2016 ), it has been reported that BMP7 induces phosphorylation of Smad1/5/8 proteins in vitro ( Yasmin et al, 2013a ). Thus, these Smad1/5/8 proteins might be involved in transmitting signaling from BMPR1A to induce LC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Runx proteins interact with Smad proteins ( Ito and Miyazono, 2003 ), Smad family proteins potentially interact with Runx3/Cbfβ2 complexes to regulate LC differentiation during BMP7-BMPR1A signaling. Although Smad2, Smad3, and Smad4 are not required for LC differentiation in vivo ( Xu et al, 2012 ; Li et al, 2016 ; Zhang et al, 2016 ), it has been reported that BMP7 induces phosphorylation of Smad1/5/8 proteins in vitro ( Yasmin et al, 2013a ). Thus, these Smad1/5/8 proteins might be involved in transmitting signaling from BMPR1A to induce LC differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Chopin and colleagues propose that RUNX3 is vital for mediating LC development, including restraining maturation, which is likely programmed by the TGF-β1-PU.1-RUNX3 transcription axis ( 105 ). Extending Chopin’s work, Zhang and colleagues proposed a collection of TFs and secondary regulators ( 106 ), including RUNX3 ( 107 , 108 ) and STAT5 ( 109 ), as important for LC development and homeostasis. Complementing Chopin’s work on PU.1, counter-regulation between C/EBP and PU.1 might be necessary for LC development, in agreement with the concept of a GRN in which stimulatory and inhibitory interactions between transcriptional partners regulate the network.…”
Section: Grns In Lc Developmentmentioning
confidence: 99%
“…TGF-β1 could regulate the expression of its downstream genes via transcription factors (TFs) 36 38 ; therefore, we searched publicly available TF datasets (PuTmiR, JASPAR, and PROMO) for potential TGF-β signalling-associated TFs that could potentially bind the miR-520h promoter, which identified 15 candidate TFs. Analysis of the mRNA expression of these TFs after stimulation of HO8910 cells with 10 ng/ml TGF-β1 for 48 h, showed that the expression of c-Myb increased the most upon treatment with TGF-β1 (by about 6-fold compared with that in untreated cells, Fig.…”
Section: Resultsmentioning
confidence: 99%